DEVELOPMENT OF PROFESSIONAL MEMORY AS AN IMPORTANT FACTOR ENSURING PERFORMANCE EFFICIENCY - Soatov Asadulloh Jabborovich (American Journals Publishing, 2023)
The article analyzes professional memory and its educational significance, the role of individual learning methods in the process of acquiring professional memory, the impact of interests in ensuring the effectiveness of activities, the importance of taking into account the interests, learning methods and individual qualities of students in educational activities.
Keywords: Profession, memory, professional memory, learning methods, knowledge, skills, qualifications, interest, motive, component, will, need.